Design and Development of a Digital Hajj Service Information System Using the TOGAF ADM Framework (A Case Study at the Ministry of Hajj and Umrah of Sukabumi City) - Zainul Bahar; Sudin Saepudin; Carti Irawan; Wisuda Jatmiko (INTERNATIONAL JOURNAL ON ADVANCED TECHNOLOGY, ENGINEERING, AND INFORMATION SYSTEM, 2026)
The implementation of hajj administrative services requires an effective, efficient, and transparent system. However, the current service process at the Ministry of Hajj and Umrah of Sukabumi City is still conducted manually, resulting in limited access to information, low service efficiency, and a high risk of administrative errors. This study aims to design a web-based digital hajj service information system architecture to improve service quality and accessibility. The study applies the TOGAF framework using the Architecture Development Method (ADM), covering nine architecture phases from preliminary analysis to architecture change management. The results of this study produce an enterprise architecture blueprint consisting of business architecture, information system architecture, technology architecture, and implementation roadmap. The proposed system enables digital management of registration, cancellation, and transfer services, improving service efficiency, administrative transparency, and public access to hajj information. The implication of this study is that the proposed architecture can serve as a strategic reference for digital transformation in public service institutions, particularly in hajj administration services.